2012
DOI: 10.1007/s00125-012-2596-z
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy at diagnosis of type 2 diabetes in Scotland

Abstract: Aims/hypothesisThe aim of this study was to examine the prevalence of and risk factors for diabetic retinopathy in people with newly diagnosed type 2 diabetes mellitus, using Scottish national data.MethodsWe identified individuals diagnosed with type 2 diabetes mellitus in Scotland between January 2005 and May 2008 using data from the national diabetes database. We calculated the prevalence of retinopathy and ORs for risk factors associated with retinopathy at first screening.ResultsOf the 51,526 people with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 25 publications
8
65
5
1
Order By: Relevance
“…Around 79% of individuals invited for diabetic eye screening in England took up the offer of screening in 2010/2011 [4]. Patients who do not attend for screening have poorer HbA 1c and blood pressure control [7] and have been diagnosed with diabetes for longer [7,8], all of which are risk factors for developing retinopathy [8][9][10][11][12][13][14][15]. These observations suggest that patients who do not attend for eye screening might be at increased risk of diabetic eye disease.…”
Section: Introductionmentioning
confidence: 99%
“…Around 79% of individuals invited for diabetic eye screening in England took up the offer of screening in 2010/2011 [4]. Patients who do not attend for screening have poorer HbA 1c and blood pressure control [7] and have been diagnosed with diabetes for longer [7,8], all of which are risk factors for developing retinopathy [8][9][10][11][12][13][14][15]. These observations suggest that patients who do not attend for eye screening might be at increased risk of diabetic eye disease.…”
Section: Introductionmentioning
confidence: 99%
“…In a disease cohort of diabetic individuals in which systolic blood pressure and Hb A1c concentrations were higher in those with than those without diabetic retinopathy, Spijkerman et al [26] did not find an association between HbA 1c levels and diabetic retinopathy in participants with screening-detected diabetes, but higher rates of arterial hypertension and dyslipidaemia were observed. In a study of the prevalence of and risk factors for diabetic retinopathy in people with newly diagnosed type 2 diabetes mellitus using Scottish national data, diabetic retinopathy was associated with male sex, systolic blood pressure, time to screening and obesity [27]. In terms of dyslipidaemia, intraretinal modified LDLs have been implicated in diabetic retinopathy, and it has been shown that extravascular modified LDLs may promote retinal pigment epithelium injury through oxidative stress, endoplasmic reticulum autophagy and apoptosis, whereas modified HDLcholesterol had protective effects [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Given that the level of CV risk increases with the duration of T2D [61,62], early and effective modification of CVD risk, whilst mitigating the risk of developing/worsening T2D, would seem sensible. Indeed, the benefits of earlier T2D screening are demonstrated by a recent analysis of data from 51,526 people with newly diagnosed T2D in Scotland, in which the majority of patients were screened for T2D within an acceptable period and the prevalence of retinopathy at first screening was significantly lower than that observed in previous studies [63].…”
Section: T2d Risk Stratificationmentioning
confidence: 93%